2020
DOI: 10.1103/physrevd.101.056017
|View full text |Cite
|
Sign up to set email alerts
|

Trident process in laser pulses

Abstract: We study the trident process in laser pulses. We provide exact numerical results for all contributions, including the difficult exchange term. We show that all terms are in general important for a short pulse. For a long pulse we identify a term that gives the dominant contribution even if the intensity is only moderately high, a01, which is an experimentally important regime where the standard locally-constant-field (LCF) approximation cannot be used. We show that the spectrum has a richer structure at a0 ∼ 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 69 publications
0
38
0
Order By: Relevance
“…In [7] we demonstrated that our gluing method indeed gives a good approximation for trident in a long pulse with a 0 ∼ 1 and linear polarization. Since the expressions presented above are valid for any field polarization, we will demonstrate this fact here for trident in a circularly polarized field, aðϕÞ ¼ a 0 ffiffi ffi 2 p fsinðϕÞ; cosðϕÞ; 0ge −ðϕ=T…”
Section: Trident In a Circularly Polarized Fieldmentioning
confidence: 74%
See 3 more Smart Citations
“…In [7] we demonstrated that our gluing method indeed gives a good approximation for trident in a long pulse with a 0 ∼ 1 and linear polarization. Since the expressions presented above are valid for any field polarization, we will demonstrate this fact here for trident in a circularly polarized field, aðϕÞ ¼ a 0 ffiffi ffi 2 p fsinðϕÞ; cosðϕÞ; 0ge −ðϕ=T…”
Section: Trident In a Circularly Polarized Fieldmentioning
confidence: 74%
“…In the following we compare the two-step part with the one-step terms, i.e., the rest of the probability. All the relevant definitions are given in [7]. As shown in [7], for a very short pulse (T ∼ 1), low to moderate intensity (a 0 ≲ 1), and "low" energy (b 0 ≲ 1), the exchange part of the one-step (i.e., the cross term between the two terms on the amplitude level that are related by exchanging the two identical particles in the final state) can be comparable to the other terms.…”
Section: Trident In a Circularly Polarized Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Depressive disorders and other kind of disorders associated to Cushing disease were: 13% of ACTH secretive pituitary tumor had a severe depression (mania, anxiety disorders, demoralization, irritable mood), quality of life of patients with Cushing's disease is compromised at 8% while 5% present a light depression and only 2.5% didn't present any symptoms of depression. [10,11,[13][14][15][16] The risk of depression at the Cushing disease patients is higher than the risk of this psychiatric manifestation at other pituitary affections. Symptoms noticed at Cushing patients were: psycho-emotional lability, physical and psychical asthenia, loss of initiative, inhibition, tendency of social isolation, amnesic difficulties, mania, psychosis, irritability, depressive ideation, panic attack, fatigue, anxiety, maladaptive personality [12,[17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%